THE EFFECTS OF PILATES TRAINING ON RESPIRATORY MUSCLE STRENGHT IN PATIENTS WITH ANKYLOSING SPONDYLITIS - Yentur, S. Baglan; Sarac, D. C.; Sari, F.; Tore, N. G.; Satis, H.; Ozturk, M. A.; Oskay, D. (Elsevier, 2020)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 03, 2020 -- ELECTR NETWORK